2012
DOI: 10.1177/1470320312460881
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the effect of glibenclamide and captopril on experimentally induced diabetic nephropathy in rats

Abstract: Hypothesis: This study aimed to elucidate the role of glibenclamide in the prevention of diabetic nephropathy and to compare it with a reference drug captopril in rats. Materials and methods: There were two main groups of rats. Control group (I) was subdivided into four subgroups which received distilled water, vehicle of streptozotocin, glibenclamide or captopril. The streptozotocin-diabetic Group (II) was subdivided into three subgroups: untreated, glibenclamide or captopril treated. Measurement of arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Similarly, in our study urine volume was significantly increased in diabetic rats compared to control rats. Glibenclamide treated diabetic rats showed a significant reduction in urine volume compared to diabetic control rats and the results of the present study are in agreement with the studies done earlier [37,38]. Dubey et al (2013) have shown that treatment of diabetic rats with oleanolic acid decreased blood glucose level and increased glomerular filtration rate [39].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in our study urine volume was significantly increased in diabetic rats compared to control rats. Glibenclamide treated diabetic rats showed a significant reduction in urine volume compared to diabetic control rats and the results of the present study are in agreement with the studies done earlier [37,38]. Dubey et al (2013) have shown that treatment of diabetic rats with oleanolic acid decreased blood glucose level and increased glomerular filtration rate [39].…”
Section: Discussionsupporting
confidence: 93%
“…Different sites of action, specifically related to blood glucose lowering abilities, may explain these findings. Furthermore, other studies have reported a conflicting action between GLI and anti-RAS medications [27]. Williams et al [28] reported that chronic GLI therapy resulted in higher blood pressure following infusion of Ang-II in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, kidney impairment may also be associated with its recognised risk factors such as hypertension, altered metabolism, alcoholism and smoking. A study has been reported that end-stage kidney disease was observed particularly in type 2 diabetic patients and requires dialysis for effective management of kidney function simultaneously with antidiabetic therapies [49] . Sometimes antidiabetic medicines cause rare side effects including renal failure, hepatic dysfunction or tissue ischemia [50] .…”
Section: ++mentioning
confidence: 99%